Comparison of Reading Performance in Students with Developmental Dyslexia by Sex - Oliveira, Adriana Marques De; Germano, Giseli Donadon; Capellini, Simone Aparecida (Universidade de São Paulo, Faculdade de Filosofia Ciências e Letras de Ribeirão Preto, 2017)
Abstract: This study aims to compare the performance of male and female dyslexic students in tests of reading words and pseudowords, and comprehension of sentences and texts. The participants were forty-eight students with dyslexia, attending 3rd grade to 5th grade of elementary school (age range 8 to 12 years old), from public and private schools, divided into: GI - 14 girls and GII - 34 boys. The researchers applied tests of Reading process assessment: reading of words, reading of pseudowords, comprehension of sentences, and comprehension of texts. The results showed evidence of difference by sex in reading of low frequency words and sentence comprehension. It was concluded that the discussion on the difference between dyslexic students by sex could be relevant in the educational context, as among the five variables, two provided information for promoting further discussion on the subject, highlighting the importance of further studies.

Resumen: Este estudio tuvo por objetivo comparar el desempeño de los estudiantes con dislexia entre los sexos femenino y masculino en las pruebas de lectura y comprensión lectora. Participaron 48 estudiantes con dislexia del 3º al 5º grado de la Enseñanza Fundamental (8 a 12 años de edad) de escuelas pública y privada, divididos en: GI - 14 niñas y GII - 34 niños. Fueron aplicadas pruebas de evaluación de lectura de palabras y pseudopalavras, comprensión de oraciones y textos, de las Pruebas de Evaluación de los procesos lectores. Los resultados indican evidencia de diferencia por sexo en las pruebas de lectura de palabras de baja frecuencia y comprensión de oraciones. Se concluyó que la discusión acerca de la diferencia entre los estudiantes con dislexia por sexo puede ser relevante en el contexto educativo, pues de las cinco variables estudiadas, dos proporcionan informaciones para alzar discusiones adicionales sobre el tema, destacando la importancia de mayores estudios.

Resumo: Este estudo objetiva comparar o desempenho dos escolares com dislexia entre os sexos feminino e masculino em provas de leitura de palavras e pseudopalavras, de compreensão de orações e textos. Participaram 48 escolares com dislexia do 3º ao 5º ano do Ensino Fundamental (8 a 12 anos de idade) de escola pública e particular divididos em: GI - 14 meninas e GII - 34 meninos. Foram aplicadas provas de avaliação de leitura de palavras e pseudopalavras, compreensão de orações e textos, das Provas de avaliação dos processos de leitura. Os resultados indicaram evidência de diferença por sexo nas provas de leitura de palavras de baixa frequência e compreensão de orações. Concluiu-se que a discussão sobre a diferença entre os escolares com dislexia por sexo pode ser relevante no contexto educacional, pois dentre as cinco variáveis estudadas, duas forneceram informações para levantar maior discussão sobre o tema, destacando a importância de mais estudos.
Comparación por Sexo del Desempeño en Lectura de los Estudiantes con Dislexia del Desarrollo
Comparação por Sexo do Desempenho em Leitura de Escolares com Dislexia do Desenvolvimento
Keywords: learning; reading; evaluation; dyslexia; sex; aprendizagem; leitura; avaliação; dislexia; sexo